2014
DOI: 10.4187/respcare.03547
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Perianesthesic Data in Subjects Undergoing Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration

Abstract: BACKGROUND: Transbronchial needle aspiration using endobronchial ultrasonography (EBUS-TBNA), a new minimally invasive diagnostic procedure, has been used to evaluate intrathoracic lymph nodes. It has been reported that EBUS-TBNA can be performed safely under sedation and provides a high level of patient satisfaction. We aimed to describe perianesthetic data, and compare results regarding the agents of subjects undergoing EBUS-TBNA under deep sedation. METHODS: After ethics committee approval, perianesthetic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 32 publications
3
9
2
1
Order By: Relevance
“…Our patients in the BIS group only presented a significantly higher BIS score at some of the recorded times (30 min and on responding to verbal orders), but there were no differences between the two groups in the overall scores, which were sufficient to generate amnesia. Although the overall satisfaction (patients who would repeat the procedure) was very high (98%), a rate similar to that found by other authors [10,19] and with no differences between the groups, the tolerance assessed using a numerical scale was higher in the BIS group (p = 0.003), which led to a higher level of comfort in these patients, probably in relationship to a shorter recovery time, and to a lower degree of dizziness.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Our patients in the BIS group only presented a significantly higher BIS score at some of the recorded times (30 min and on responding to verbal orders), but there were no differences between the two groups in the overall scores, which were sufficient to generate amnesia. Although the overall satisfaction (patients who would repeat the procedure) was very high (98%), a rate similar to that found by other authors [10,19] and with no differences between the groups, the tolerance assessed using a numerical scale was higher in the BIS group (p = 0.003), which led to a higher level of comfort in these patients, probably in relationship to a shorter recovery time, and to a lower degree of dizziness.…”
Section: Discussionsupporting
confidence: 72%
“…Our longer mean duration may have been due to the learning curve of the residents and the systematic triple puncture of all lymph node stations punctured, which included lymph nodes not captured on the positron emission tomography scan. As in our study, other authors have found no correlation between adverse events and advanced age or higher ASA scores [10,13,41], although OSA did correlate with adverse events. Our results, which made it possible to reduce the dose of drugs in the BIS group, suggest that the lower incidence of adverse events in this group is linked to the lower dose of the drugs used.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…Although various sedative agents have been employed for EBUS-TBNA, any ideal agents or protocols have not yet been determined for sedation [2,3]. Different disturbing conditions might appear due to high level anxiety.…”
Section: Introductionmentioning
confidence: 99%